Improving the Marketing Performance of Village-Owned Enterprises and Tourism Villages by Strengthening Social Media Marketing Skills and Service Quality - Santoso, Adi; Hidayah, Riski Taufik; Sunarya, Yaya (Edumedia Solution, 2025)
This community service program aims to empower the Village-Owned Enterprise and Tenjolaya Tourism Village by strengthening social media marketing skills and improving service quality. Tenjolaya Village has significant natural and cultural tourism potential. However, tourism destination management faces various challenges, particularly in digital marketing and service quality, resulting in under-utilization of this potential. This activity actively involves the community in training, mentoring, and developing marketing strategies and tourism services. The methods used in this community service program are participatory, including intensive training on social media marketing, service quality improvement workshops, ongoing mentoring, and the formation of social media and tourism service management teams. The training focuses on utilizing social media platforms such as Instagram, Facebook, and TikTok for tourism promotion. At the same time, the workshop aims to improve the community's skills in providing excellent service to tourists. Intensive mentoring is provided to ensure effective and sustainable strategy implementation. The expected results of this activity are an increase in the number of tourist visits through effective digital promotion, increased tourist satisfaction through quality services, and community empowerment in independently managing tourism potential. This community service activity aims to improve the performance of the Village-Owned Enterprise and tourist villages and empower the community to become independent in managing its tourism potential. This program is expected to significantly impact the economic development and well-being of the Tenjolaya Village community through a systematic and sustainable approach